Infected congenital mucocele of the nasolacrimal duct. - Meyer, J R; Quint, D J; Holmes, J M; Wiatrak, B J (American Journal of Neuroradiology, 1993)
The authors report their experience with an infant presenting with an infected nasolacrimal duct mucocele, emphasizing correlation of clinical, CT, and surgical findings. CT is the imaging modality of choice to demonstrate the triad of 1) a cystic medial canthal mass, 2) dilatation of the nasolacrimal duct, and 3) a submucosal nasal cavity mass; findings which are diagnostic of this entity. A brief review of the relevant embryology is also presented.